Genetic Analysis of Heterotic Crosses in Rice (Oryza sativa L.) under Rainfed Ecosystem - Arya, Madhuri; Singh, Aradhana; Singh, H. C.; Parveen, Shama; Kumar, Manoj; Ram, Mukh; Shalini, Shipra (International Journal of Bio-resource and Stress Management, 2023)
An experiment consisting of fifteen testers, three lines and their forty five crosses was conducted at crop research farm of Birsa Agriculture University, Kanke, Ranchi, Jharkhand during kharif season. Each parent and F1s were sown in five rows plot of 5.0×1.0 m2 spaced at 20×15 cm2 between rows and plants respectively. The experiment was laid out in Randomized Complete Block Design replicated thrice. All the recommended packages of practices were adopted to raise a good crop except irrigations as crop was irrigated through rains itself. The observations were recorded on five randomly selected plants from each of parents and F1 crosses on fifteen yield and yield attributing traits. Heterosis over mid parent for yield and its components was calculated as usual procedure. Cross combinations namely; BAU-274-92×IR-36 gave significantly positive heterosis to the tune of 31.39% followed by BR-8×IR-36 (27.57%) and BR-8×BD-202 (27%) and BAU-211-90×IR-36 (27.44%), BAU-211×BD- 202 (25.83%) and BAU-269-92×IR-36 (25.97%) for grain yield plant-1. The gca status of the parents involved revealed high×high, high×low and low×low combinations means involvement of both additive and non additive gene effects. The combinations can be further improved through simple selection procedures (additive×additive) or after advancing the generations through transgression effects.